The Relationship between Truth and Art in Martin Heidegger's Thought: An Analysis of Relevance to the Existence of AI Chatbots - Rifqi Khairul Anam (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2025)
This research explores the relationship between truth and art in Martin Heidegger's philosophy, particularly its relevance to the existence of AI chatbots. Heidegger redefines truth not as static correspondence but as aletheia—unconcealment, where entities reveal themselves through processes such as art and language. Art, for Heidegger, is the primary means by which truth is disclosed, opening up new worlds and perspectives beyond ordinary perception. In contrast, modern technology, epitomized by AI, operates through Enframing (Gestell), which reduces beings to resources, obscuring their authentic revelation. The central question of this research is whether AI chatbots, such as ChatGPT and Gemini, can engage in the unconcealment of truth as Heidegger describes it or if they are merely mechanical simulations of human creativity. Through an analysis of Heidegger’s concepts of aletheia and Gestell, the study examines the ontological implications of AI in relation to human existence and the unveiling of truth. The research finds that, despite their ability to generate text that simulates human conversation, AI chatbots lack the existential grounding of Dasein—the human condition necessary for true unconcealment. Therefore, while AI may mimic creativity, it cannot genuinely participate in the revelation of truth in Heideggerian terms. The study concludes by emphasizing the irreplaceable role of human engagement in the process of aletheia, which AI systems, by nature, cannot replicate, offering a critique of AI’s impact on understanding of art, truth, and human authenticity.